The burden of dengue: Jundiaí, Brazil - January 2010 - Arenas,Christian Julián Villabona (2012)
OBJECTIVE: To study the antibody prevalence against dengue in the municipality of Jundiaí, São Paulo, Brazil, due to the low number of official confirmed autochthonous cases. METHODS: A serological study on dengue infection was conducted during January 2010 and previous reports on dengue and entomological surveillance during that period were reviewed. RESULTS: A prevalence of 7.8% IgG positive (68:876) was found. Furthermore, based on the detection of IgM antibodies in five samples, it was observed that the incidence of dengue in the city at the time of the survey contrasts with the absence of notifications by local health authorities over the same period of time. CONCLUSION: These results highlight the discrepancies between the actual and the detected number of dengue infections, possibly due to significant numbers of asymptomatic infections aggravated by difficulties with dengue clinical diagnosis.